Mitigation of struvite formation in palm oil mill effluent (POME) treatment facilities - Ngatiman, Muzammil; Jami, Mohammed Saedi; Abu Bakar, Mohd Rushdi; Vijaya, Subramaniam; Soh, Kheang Loh (2018)
Struvite formation or generally known as scaling in palm oil mill effluent ( POME) treatment system has long been identified to cause adverse impact on the efficiency of the POME treatment process. Its occurrence has become more common in recent years with the increase of nationwide palm oil milling capacity. This study determines the characteristic of struvite sample from a typical POME treatment facility and examines the influence of pH and temperature on these struvite samples. Struvite samples were collected from a piping set up of a POME treatment facility in a 50 tph palm oil mill. X-ray diffraction ( XRD) , energy dispersive spectroscopy ( EDS) and solubility analysis were carried out on the sample. Composition of phosphorous element was found at 22. 8% . Other elements were magnesium ( Mg) , 20. 4% , carbon (C), 2.3%, hydrogen (H) 3.5% and nitrogen (N), 2.0%. Maximum solubility of 270.4 mg/L was achieved at pH of 3 and temperature of 40oC while minimum solubility of 122.1 mg/ L was recorded at pH 7 and temperature of 25oC. The study concludes that although struvite is currently a problem in palm oil mill, it possesses a significant economic benefit as an alternative source of valuable fertilizer material that can be further exploited.